1998
DOI: 10.1007/bf02495646
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and electronic structures and conformational analysis of derivatives of 9-nitroanthracene, anionic σ-complexes

Abstract: Potassium 10-methoxy-9-nitroanthracenide was studied by X-ray diffraction analysis. The central ring of the anthracene fragment adopts an asymmetrically flattened boat conformation. The bond lengths in the C(Ar)--C(NO2)--C(Ar) fragment are indicative of the presence of conjugation between the 7t-systems of the benzene rings and the nitro group owing to a substantial contribution of the aci form to the structure of the nitro group.Quantum-chemical calculations of anionic cr-complexes of 9-nitroanthracene deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The C(5)−N(2) bond 1.399(1) Å is shorter than the C(7)−N(3) bond 1.414(1) Å. It should be noted as well that both C−NO 2 bonds are significantly shorter in the anion 2 as compared to the anionic σ-complex 1 (see also 9,43 ), but are much longer than the C−N bond (1.36(2) Å) in the Meisenheimer complex of 9-nitroanthracene . This indicates an essential increase of the partially double character of the C−NO 2 bonds with expansion of the aromatic π-system.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The C(5)−N(2) bond 1.399(1) Å is shorter than the C(7)−N(3) bond 1.414(1) Å. It should be noted as well that both C−NO 2 bonds are significantly shorter in the anion 2 as compared to the anionic σ-complex 1 (see also 9,43 ), but are much longer than the C−N bond (1.36(2) Å) in the Meisenheimer complex of 9-nitroanthracene . This indicates an essential increase of the partially double character of the C−NO 2 bonds with expansion of the aromatic π-system.…”
Section: Resultsmentioning
confidence: 87%
“…Previous theoretical studies of the MC demonstrated some contradictions between results of calculations using different semiempirical ,, and ab initio ,, methods as well. For example, the study of the nucleophilic aromatic substitution reaction between 4-Cl−Ph-CO−SMe and CH 3 COO - by the PM3 and DFT methods indicated a formation of the stable MC during reaction.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation